Low cost hand orthotic device to improve hand function of stroke patients. - Megalingam, Rajesh Kannan; Baburaj, Abilash Mookola; Mattathil, Anoop; Hari, Anirudh; Sreekanthan, Karthik; Koppaka, Ganesh Sai Apuroop (Technology & Disability, 2019)
Providing a cheaper and comfortable solution in the rehabilitation process of stroke patients to improve their hand function is a challenging task. Employing physiotherapists to improve hand function of stroke patients once they are discharged from the hospital is a costly affair in developing and underdeveloped nations. In this research work the design, development and control of a low cost, self-actuated hand orthotic device was presented that can be used in the rehabilitation process of stroke patients in improving their hand functions. In this paper a single degree of freedom, low cost, easy to wear, easy control, auto-actuating orthosis was designed on the basis of the abduction and adduction method. A graphical user interface (GUI) was developed for self-actuation and it would simplify the control of the device to alter the angle and speed of the carpometacarpal joint during the therapy of stroke and surgery sufferers by the physiotherapists at hospitals. The same can be employed by users post hospital treatment at their residences without the need to hire physiotherapists. The experiments conducted in the lab and tests with patients at the rehabilitation center demonstrate the success of the system. Given its excellent comfortableness, easy-of-use, light-weight and affordable cost, this device can be used to address the rehabilitation issues of the patients with hand paralysis, particularly in developing countries post hospital treatment.